PENGARUH MARKETING MIX DAN BANDWAGON EFFECT TERHADAP BRAND EQUITY DAN VOTING INTENTION DALAM KANDIDAT PEMILIHAN UMUM PRESIDEN DAN WAKIL PRESIDEN 2014 - Ayu Febri Puspitasari; Suharyono . (REFORMASI, 2014)
Marketing activities required to sustainability andexistence of the organizationin order to survive and remain accepted by society. With the times, marketing is not only used by profite companies, but has been widely used by non-profit institutions such as NGO, educational institutions, museums, hospitals, and politics is no exception. This research use dexplanatory methode. The locationof this researchis East Java which basedon the consideration that it is the second most residents province. Beside that East Java is barometer of Indonesia elections. The population of this study were all residents in East Java that has the suffrage to vote( aged 17 years and olderor married) and have entered into the voters list (DPT) in the election of Presidentand Vice President in 2014. Based on the provisions of the Commission, the number of voters remain in East Java by 30,545,935 people. The sample size of this study using Slovin formula, in order to obtaina minimum number of 124 people. The research was divided into16 clusters, where each clusteris taken 8 people, so that the sample rounded to 128 people. Furthermore, the sampling technique used in this study are Multistage Random Sampling(MRS). The results ofthis study were1) Marketing Mix had significant effect on Brand Equity candidate, 2) Bandwagon Effect had significant effect on Brand Equity candidates, 3) Marketing Mix had no significant effect on Voting Intention candidates, 4) Bandwagon Effect had no significant effect on Voting Intention, 5) Brand Equity had significant effecton Voting Intention.